Pengaruh Literasi Keuangan, Financial Tekhnologi dan Gaya Hidup Hedonisme terhadap Perilaku Keuangan Mahasiswa - Siti Nur Ariska; Jumawan Jusman; Asriany Asriany (Politeknik Ganesha Medan, 2023)
In today's modern era, students must have financial intelligence, namely intelligence in managing finances. When a student is able to make the right decisions about finances, there will be no financial problems in the future and is able to show healthy financial behavior and is able to determine which needs are not wants. However, not a few college students tend to spend their money for things they want instead of what the brand needs. Therefore, this study aims to examine the influence of financial technology on student financial behavior, financial literacy on student financial behavior, and hedonistic lifestyle on student financial behavior. The data used in this study were primary data obtained from questionnaires. This research uses quantitative research methods where the research results are presented in the form of numbers or statistics. The total number of populations in this study is not yet known, so sampling was taken using non-probability samples and 178 respondents were obtained from students in palopo city. Hypothesis testing uses structural Equation models. The results of the research in this study were tested using SmartPLS. Based on the results of this study, it resulted that financial technology has a positive and significant effect on student financial behavior, financial literacy has a positive and significant effect on student financial behavior and hedonistic lifestyles have a positive and significant effect on student financial behavior.